Co-producing, curating, and defining design knowledge in an online practitioner community. Issue 1 (2nd January 2019) - Gray, Colin M.; Kou, Yubo
ABSTRACT: As co-design and other participatory design practices increasingly make design outcomes more accessible to everyday citizens, it is also important to understand how designers negotiate the value of design knowledge that undergirds design action and share this knowledge within their own community to facilitate and evolve their practices. In this study, we analyze UX practitioners' interactions on Reddit, including patterns of resource sharing and curation that point towards a collective construction of UX as a design discipline. We identified how knowledge from diverse sources was selected and shared with the subreddit community (co-production); the resources that community members engaged with and to what extent (curation); and the collective body of knowledge that characterised the design community (definition of design knowledge). We found that boundary work that sought to define the value of UX knowledge often took place at the periphery of shared resources, either expanding or rearticulating the boundary of UX knowledge in relation to trends in employment and nascent professionalisation. Implications of this work for the co-creation of knowledge to support design practices are considered, focusing on how design knowledge concomitantly shapes and is shaped by client-directed design action.